Method development and validation of simultaneous estimation of acetaminophen and behydrocodone in tablet dosage forms - B.Bhanu Priya; R.V Valli Kumari; M.Satish Kumar (International Journal of Pharmacy and Analytical Research, 2022)
A RP-HPLC procedure is developed, validated and applied for simultaneous estimation of acetaminophen and benzhydrocodone in tablets. Procedure is based on separation and analysis of acetaminophen and benzhydrocodone in Hibar C18 column and 0.1M K2HPO4: methanol (65:35v) mixture as stationary and mobile phase, respectively. The elution time values for acetaminophen and benzhydrocodone were 3.692min and 4.956 min, respectively. Linear ranges for acetaminophen and benzhydrocodone are 162.5-487.5 µg/ml and 3.06-9.18 µg/ml, respectively. The values of sensitivity were 0.311 µg/ml (LOD) and 1.035 µg/ml (LOQ) for acetaminophen and 0.036 (LOD) µg/ml and 0.121 µg/ml (LOQ) for benzhydrocodone. The validation parameters are tested using guidelines of ICH. The validation values obtained are well acceptable. The method proved as suitable procedure for assay acetaminophen and benzhydrocodone in tablet dosage forms with good assay percent values.